Ultrasound-assisted adsorption on porous ceramic for removal of iron in water. Issue 8 (3rd April 2022) - Negris, Luana; Santos, Hélisson N.; Picoloto, Rochele S.; Alves, Felipe E. A.; Flores, Erico M. M.; Santos, Maria F. P.; Vicente, Maristela A.
ABSTRACT: This study proposes the use of an ultrasound-assisted adsorption system coupled to porous ceramic fragments to improve the removal of iron from FeSO4 aqueous solution. Ultrasound was applied using an ultrasound bath at a low frequency (37 kHz, 330 W). The optimized conditions for Fe removal were achieved by 7 g of adsorbent, 40 min of sonication, 20 mg L –1 of initial Fe concentration, and 30 °C of reaction temperature. After optimizing the conditions, the method was applied for the removal of iron in groundwater. A central composite design and response surface methodology were used to evaluate the degree to which different variables had a significant effect on iron removal. The efficiency of iron removal using the selected conditions for FeSO4 solution was near to 100%. However, for groundwater samples, the maximum iron removal efficiencies of the system with and without ultrasound were 80.7% and 51.1%, respectively, indicating that the adsorption with ultrasound was significantly higher than that without ultrasound. It was shown that the proposed ultrasound-assisted adsorption system can be used to enhance the removal of inorganic iron from groundwater. GRAPHICAL ABSTRACT: UF0001